The Influence Of Human Resource Development, Leadership Style And Motivation On Work Achievement Of Civil Servants At The Ministry Of Religion Office In Bengkulu City - Tamara, Agina; Susanti, Neri; Subhi, Ramadan (Journal of Multidisciplinary Research, 2025)
This study aims to determine the effect of human resource development, leadership style and motivation on the work achievement of civil servants at the Ministry of Religion Office in Bengkulu City. This type of research is a type of quantitative research. The data collection method in this study used a questionnaire technique, with a sample of 105 respondents. The results showed that multiple linear regression Y = 21,987 + 0.140 X1 + 0.313 X2 + 0.128 X3 + 0.3,841. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the variables of Human Resources Development (X1), Leadership Style (X2) Motivation (X3) on Work Achievement (Y) of civil servants at the Ministry of Religion Office in Bengkulu City. The test results of human resource development (XI) show tcount 2.350> ttable 1.65964 and sigfinication 0.021 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that human resource development has a positive and significant effect on the Work Achievement of the State Civil Apparatus of the Bengkulu City Ministry of Religion Office. The results of the leadership style test (XI) show tcount 5.086> ttable 1.65964 and sigfinication 0.000 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that leadership style has a positive and significant effect on the Work Achievement of civil servants at the Ministry of Religion Office in Bengkulu City. The results of the motivation test (XI) show tcount 2.143> ttable 1.65964 and sigfinikasi 0.035 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that motivation has a positive and significant effect on the Work Achievement of civil servants at the Ministry of Religion Office in Bengkulu City. Based on the comparison of the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 14.636> 2.46, it is concluded that it accepts the hypothesis, meaning that there is a simultaneous influence between Human Resource Development (X1), Leadership Style (X2) Motivation (X3), the value is 0 (zero), on Work Achievement (Y) of civil servants at the Ministry of Religion Office in Bengkulu City.